Ptychographic X-ray microscopy with the vacuum imaging apparatus HORST - Gorniak, Thomas; Rosenhahn, Axel (Zeitschrift für physikalische Chemie, 2014)
Imaging is one of the key drivers for new scientific insights - from - the observation of distant stars in astronomy to microscopic studies - of sub-cellular structures in biology. In the latter case, X-rays are - a versatile probe due to their small wavelength and thus high spatial - sensitivity. We give an overview of applicable lensless, coherent - imaging approaches relying on scattering with a focus on ptychographic - microscopy and discuss the experimental requirements for the soft - X-ray scattering experiment HORST. Besides the experiment itself, we - highlight the importance of sample environments, especially when - biological specimens are investigated. Here, the water window is of - central importance. In addition to exploitation of the contrast and - resolution, resonant ptychography allows to distinguish chemical - species at high spatial resolution with both phase and amplitude - contrast.
Gesehen am 23.10.2020